Analysis Income Palm Sugar Business Makmur Village, Palolo District, Sigi District - Muhilannuri; Rita Yunus; Chaerul Anam; Yunus Sading; Failur Rahman (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze income palm sugar business in Makmur Village, Palolo District, Sigi Regency. This research was conducted in Makmur Village, Palolo District, Sigi Regency. This type of research is descriptive research type. Data collection techniques used observation and interviews from palm sugar entrepreneurs in the prosperous village, Palolo subdistrict, Sigi district. The data source for this research is primary data. Data analysis in this research uses the income and revenue analysis method. The results of the calculation of revenue from the palm sugar business amounted to IDR 1,800,000 . The calculation results for expenses from production costs amount to Rp. 885,000 , and the income results obtained from revenue costs are less than total costs and produce income of Rp . 898,889